The urgency of religious and cultural science in STEM education: A meta data analysis - Woro Sumarni; Zulfatul Faizah; Bambang Subali; W. Wiyanto; Ellianawati Ellianawati (Institute of Advanced Engineering and Science, 2020)
The 21st century education engages students to have higher order thinking and scientific literacy skills. However, these abilities in Indonsia are still relatively low, especially student’s scientific literacy skills. One solution to the problem of low scientific literacy skills in Indonesia is the application of STEM education. However, as technology advances pursued in STEM education, religious and cultural sciences increasingly separate themselves from science. Cultural science is rarely implemented in learning so that many students do not know their own culture. The contra between science and religion also makes students’s perception of religion and science are two independent knowledge and cannot be united. Through literature studies that have been carried out from various journal article search sites, this article discusses how important religious and cultural sciences are to be implemented into STEM education. The relationship between religion and science, culture and science, culture and religion and the urgency of religion and culture in STEM education are also discussed in this article. The results of this study propose solutions so that science education can be implemented with RE-STEM learning to overcome the gap between religion, culture and science. So, that students will have a more balanced knowledge in religion, ethnoscience and science from RE-STEM integration.